세계 게임 심의제도 비교분석 - 김찬수(Chan-Soo Kim); 박태순(Tae-Soon Park) (한국콘텐츠학회 논문지, 6(5), 2006)
Almost all of the nations run a game screening system which is characteristic depending on their communication policy. This article attempted comparative analysis about major nation's game screening systems by comparing three main aspects of their communication policy which are freedom of expression, complete opening of the contents to the public, and the balance between protection of adolescent and promotion of industry. It is shown that the screening system of USA, Europe and Japan stick well by the basic principles of communication policy, on the other hand Korea, South Africa Republic and Australia have some points that need improvement. 게임심의제도는 거의 모든 국가에서 운영되는데, 각 국가의 커뮤니케이션 정책에 따라 그 운영형태는 각각 상이하다. 본고에서는 주요 국가의 게임심의제도를 표현의 자유, 콘텐츠 완전공개, 청소년보호/산업 진흥의 균형이라는 세 측면에서 비교분석하였다. 그 결과 미국, 유럽, 일본 등의 제도가 커뮤니케이션 정책의 기본원칙들을 충실히 지키는 편이었으며, 우리나라와 남아공, 호주 등은 아직 개선되어야 할 점이 많이 나타났다.